2017
DOI: 10.15446/profile.v19n1.54184
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Internet Usage of Pre-service Language Teachers With Teachers of Other Subjects: Distance Learning vs. On-Campus Learning

Abstract: Comparación del uso de Internet entre docentes de idiomas en formación y docentes de otras áreas: educación a distancia frente a presencial Mehmet Firat1* Harun Serpil2 Los maestros juegan un papel crucial para facilitar que las personas adquieran competencias adecuadas para el uso de Internet. Esto requiere que los maestros mismos sean diestros en dichas competencias. El propósito de este estudio es investigar el uso de Internet, a distancia y dentro del campus, de los futuros profesores. Un total de 789 doce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…This finding is congruent to Onwuagboke et al (2014) who found no statistically significant difference in the frequency of internet usage among age groups (16)(17)(18)(19)(20)(21)(22)(23)(24) and greater than 25 years). The year of study did not significantly affect extent of internet usage contrary to Firat and Serpil (2017) finding who established significant differences with respect to year (class) of study -internet usage increased with year of study. Neither the type of source of internet services discriminated between pre-service teachers" extent of internet usage or owning a computer (or not) did not determine internet usage.…”
Section: Research Question 3 What Demographic Factors Affect Pre-servcontrasting
confidence: 95%
See 2 more Smart Citations
“…This finding is congruent to Onwuagboke et al (2014) who found no statistically significant difference in the frequency of internet usage among age groups (16)(17)(18)(19)(20)(21)(22)(23)(24) and greater than 25 years). The year of study did not significantly affect extent of internet usage contrary to Firat and Serpil (2017) finding who established significant differences with respect to year (class) of study -internet usage increased with year of study. Neither the type of source of internet services discriminated between pre-service teachers" extent of internet usage or owning a computer (or not) did not determine internet usage.…”
Section: Research Question 3 What Demographic Factors Affect Pre-servcontrasting
confidence: 95%
“…Examination of Table 8 reveals that all demographic variables were not statistically significant determinants for internet use by pre-service teachers. Notably being male or female does not determine internet usage in agreement with other findings (Firat & Serpil (2017) ;Helsper, 2010;Ogunlade, Fagbola, Ogunlade & Amosa, 2015;and Onwuagboke et al, 2014). This finding is contrary to that of Adediran and Kehinde (2014) who found significant difference between male and female participants with male higher usage than their female counterparts.…”
Section: Research Question 3 What Demographic Factors Affect Pre-servsupporting
confidence: 82%
See 1 more Smart Citation
“…Language learning through social networks has been studied by researchers (e.g. Firat & Serpil, 2017;Khabiri & Khatibi, 2013;Yousefzadeh, 2012). Greenhow (2011) said that social networking sites support learning and new technologies are very useful for educational goals.…”
Section: Social Networking Sitesmentioning
confidence: 99%
“…In regards to teachers who are supportive of practices mediated by technology, Firat and Serpil (2017) did a comparative study of internet usage in different groups of teachers. They assert that teachers need to be internet literate so as to help their students gain internet competency.…”
Section: Technology and Language Learning Appsmentioning
confidence: 99%